Objetos de conhecimento do componente curricular ciências da natureza, presentes em obras da literatura infantil - Santos, Leda Jane dos (2021)
Children's Literature is present in the literacy cycle of Elementary School and can be used in the Teaching of Natural Sciences for the development of children's scientific thinking. Focusing on the Early Years of Elementary Education, Literacy Cycle (1st to 3rd year), this research approached the contextualization of the knowledge of Natural Sciences present in Children's Literature. The curricular component of the Sciences of Nature of the Curriculum of the City of São Paulo for Elementary Education Early Years, emphasizes that the objects of knowledge must start from Scientific Literacy (AC) with a literary language, which justifies our concern in this research. Thus, we sought to investigate the possible relationships between the objects of knowledge of Natural Sciences proposed in official documents and the contents of images and texts conveyed in Children's Literature books that can facilitate the work of the teacher in the student's AC and LC process. It is believed that children’s literature contributed to world comprehension and this includes the natural phenomena comprehension when the books bring sciences contents. Our general objective was to identify in the Children's Literature the objects of knowledge of Sciences proposed in the official documents, literacy cycle, which enable the teacher to work with skills related to the students' AC and LC. As specific objectives we propose to: (1) Identify what resources Children's Literature presents for access to the Natural Science knowledge objects present in the Matter, Energy and their Transformations axes; Cosmos, Space and Time; Life, Environment and Health; (2) Relate the images with the text of each literary work analyzed in relation to the contents of Sciences from the 1st to the 3rd year of the Initial Years of the Literacy Cycle; (3) Point out attitudes and values contained in the works that contribute to the transformation of society, as proposed by the official documents. The research guided by qualitative approach of documental analysis type. The results showed that the contents of Science permeate the analyzed works, and that to make them attractive, thought-provoking, creative, playful and reflective, it will be up to the teacher to identify and approach these contents with the children from the literary language, and take them understanding of natural phenomena present in the Teaching of Natural Sciences (ECN).